A Matter of Comprehensive Informed Consent: Short-Term Mortality Rates With Definitive Treatment Options in Elderly Stage I NSCLC. (November 2019) - Dalwadi, Shraddha M.; Savjani, Ricky R.; Bernicker, Eric H.; Butler, Edward B.; Teh, Bin S.; Farach, Andrew M.
Abstract : Background: Although lobectomy is the standard of care in stage I non–small cell lung cancer (NSCLC), medical comorbidities increase surgical risk in elderly patients. No population-based studies compare short-term mortality (STM) for surgery (STM-S), radiation (STM-R), and observation (STM-O) in elderly patients with stage I NSCLC. Methods: A total of 60, 466 biopsy-proven stage I NSCLC cases diagnosed between 2004 and 2012 were retrieved from the Surveillance, Epidemiology, and End Results Program. Patient characteristics were compared using χ 2 test. Age was divided into 5-year subsets (60 to 64 to 90+ y) for analysis. Similar to other series, STM was defined as death within 2 months of diagnosis. Univariate and multivariate analysis for STM was performed using odds ratio, Kaplan-Meier actuarial method, and Cox proportional hazard ratio. Results: In younger patients, STM-S rates are lower compared with STM-R (1.6% vs. 3.4% in patients 60 to 64 y, P <0.001). However, STM-S rates surpass STM-R with increasing age (up to 8.1% vs. 2.3% in patients 90+ y, P <0.001) becoming significant in the 75- to 79-year age group (4.7% vs. 2.2%, P <0.001). There is an inflection point in the 65- to 69-year age group where STM-S and STM-R rates are similar (2.6% vs. 3.0%, P =0.090). STM for observation reflected the poor health of this cohort with high STM rates in all age groups (19.5% for age 60 to 64 y to 25.3% for age 90+ y, P =0.005). Sex, race, Hispanic ethnicity, age group, and treatment were associated with higher STM on the multivariable analysis (all P <0.001). Conclusion: STM in elderly stage I NSCLC patients treated with surgery increases with advancing age but remains stable for patients receiving radiation. Given the success of stereotactic body radiation therapy, radiation should be considered for patients with high STM risk associated with surgery.